Pathophysiological changes and injury markers for acute lung injury from blunt impact in infant rabbits - Wang, Ke; Huang, ZhenPeng; He, JiaWei; Kong, LingWang; Chen, Mingwei (Frontiers in Pediatrics, 2024)
Background: Traffic accidents, particularly blunt impacts, cause serious injuries in children. We aimed to assess inflammatory and injury responses in infant rabbits subjected to acute lung injury resulting from blunt impact, with the goal of identifying potential circulatory injury markers.Methods: Forty 4-week-old infant rabbits were subjected to a right chest impact using a Hopkinson bar with 2600 g. Computed tomography was employed to assess injury severity. Pathological changes were observed using hematoxylin and eosin staining in the control, 0, 24, and 72 h groups, post-injury. Immunohistochemistry was used to examine surfactant protein A (SP-A) changes in right lung tissues and upper main bronchi. Serum levels of interleukin-6 (IL-6), IL-8, and SP-A were measured using ELISA within 24 h post-injury in the control, 0 h, and 24 h groups.Results: Following blunt injury, significant increases were observed in blood white blood cell count (F = 101.556, P < 0.01) and neutrophil percentage (F = 104.228, P < 0.01), which gradually decreased after 24 and 72 hours. The lung wet/dry weight ratio indicated significant edema (F = 79.677, P < 0.01), corroborated by hematoxylin and eosin staining showing edema, exudation, and marked granulocyte infiltration in the control, 0 h, 24 h and 72 h groups. SP-A levels decreased rapidly at 0 hour, and recovered between 24 and 72 hours in the right lung tissues (F = 6.7, P < 0.05) , left lung(F = 15.825, P < 0.05) and upper main bronchi (F = 59.552, P < 0.01). The ELISA results showed increasing trends for the control and 0 h groups, while decreasing trends were observed in 24 h group for IL-6 (F = 58.328, P < 0.01) and IL-8 (F = 41.802, P < 0.01). Conversely, SP-A exhibited a decreasing trend in the control and 0 h groups but increased in the serum of 24 h group (F = 52.629, P < 0.01).Discussion: In cases of direct chest trauma in infant rabbits, particularly mild injuries without rib fractures. SP-A levels correlated with pathological changes across all groups and may serve as biomarkers for pediatric blunt lung impact.